How to Teach Morality - Georg Lind (Review) - Cobos, Semiramis Llanos (ETHICS IN PROGRESS, 2016)
In his recent book, Georg Lind develops the philosophical and methodological foundations of the Konstanz Method of Dilemma Discussion®, which provide both theoretical and practical work frames for developing moral and democratic competencies.